2020
DOI: 10.1051/e3sconf/202016613027
|View full text |Cite
|
Sign up to set email alerts
|

FinTech as an innovation challenge: from big data to sustainable development

Abstract: Driving force of human society development is elimination contradiction between unlimited usage of natural resources during economic activity of enterprises, environment pollution as a result of such activity and limited natural, energy and other resources. Research results on economic and environmental issues of green business management showed that there are several basic types of problems at present which arise at enterprises during collecting and processing data on the results of their activities. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…By paying attention to economic-financial variables, EPS gives a very low result due to the large number of total common shares outstanding, with an average of 187 million. FinTech companies are growing (Ignatyuk et al, 2020), which supports the PER and ROE averages. Although the high average PER value may indicate that these companies are overvalued, both the context and economic situation would indicate that investors estimate that these companies' profits will rise in forthcoming years.…”
Section: The Samplementioning
confidence: 57%
“…By paying attention to economic-financial variables, EPS gives a very low result due to the large number of total common shares outstanding, with an average of 187 million. FinTech companies are growing (Ignatyuk et al, 2020), which supports the PER and ROE averages. Although the high average PER value may indicate that these companies are overvalued, both the context and economic situation would indicate that investors estimate that these companies' profits will rise in forthcoming years.…”
Section: The Samplementioning
confidence: 57%
“…For example, FinTech needs input from the public and private sectors, even though the private sector can develop technology programs and build infrastructure quickly (Ignatyuk, Liubkina, Murovana, & Magomedova, 2020). The private sector led the way in developing businesses and sharing economy platforms such as Uber, Lyft, and Airbnb, while governments implemented regulatory changes (Koopman, Mitchell, & Thierer, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Crawford (2013) mentioned, big data analysis may be biased depending on agendas. Big data analysis is limited by existing way of collecting and storage, existing infrastructure, and the lack of experience in green entrepreneurship, alternative energy, and green production (Ignatyuk et al, 2020). A study by Brynjolfsson et al (2017) also suggested that there are four possible explanations for the AI productivity paradox: false expectations, measurement errors, centralized distribution, and dissipation of rent, and implementation and restructuring delays.…”
Section: Green Economic Developmentmentioning
confidence: 99%